2006
DOI: 10.2353/ajpath.2006.050338
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Calcification in the Rat Subdermal Model Is Accompanied by Up-Regulation of Degradative and Osteogenic Cellular Responses

Abstract: Calcification of vascular elastin occurs in patients with arteriosclerosis, renal failure, diabetes, and vascular graft implants. We hypothesized that pathological elastin calcification is related to degenerative and osteogenic mechanisms. To test this hypothesis, the temporal expression of genes and proteins associated with elastin degradation and osteogenesis was examined in the rat subdermal calcification model by quantitative real-time reverse transcription-polymerase chain reaction and specific protein as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 56 publications
3
51
0
1
Order By: Relevance
“…We have extensively studied mechanisms of elastin calcification and have shown that matrix degrading enzymes such as MMPs are involved in elastin calcification [12,48]. In this study, an initial inflammatory response (macrophage infiltration) seen at 7 days was reduced by 28 days.…”
Section: Discussionmentioning
confidence: 65%
“…We have extensively studied mechanisms of elastin calcification and have shown that matrix degrading enzymes such as MMPs are involved in elastin calcification [12,48]. In this study, an initial inflammatory response (macrophage infiltration) seen at 7 days was reduced by 28 days.…”
Section: Discussionmentioning
confidence: 65%
“…At day 21, harvested constructs were ground into powder in liquid nitrogen, extracted in RIPA buffer containing protease inhibitors (Invitrogen, Carlsbad, CA), and then assayed for total protein content using a BCA assay kit (Thermo Scientific). 19 Volumes equivalent to 3 mg of protein were loaded under reduced conditions into 4%-12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gel for LOX analysis and 10% SDS-PAGE gel for MMP analysis, along with a prestained molecular weight ladder (Invitrogen). The gels were then transferred wet onto polyvinylidene fluoride membranes.…”
Section: Western Blotting For Lox and Mmps-2 And -9mentioning
confidence: 99%
“…Limited attention has been devoted to discerning the activities of enzymes on polymer degradation [18,19] and many other related issues have yet to be explored. It was previously reported that the activities of various capsule-borne enzymes were elevated in a rat subdermal model two weeks after material implantation [20]. However, abnormal expressions of many oxidative and hydrolytic enzymes are associated with diseases.…”
Section: Assessment Of Enzyme Activitiesmentioning
confidence: 99%